ASSOCIATION BETWEEN ELEVATED HIGH SENSITIVITY CARDIAC-TROPONIN I LEVELS AND INCREASE IN LEVELS OF C-REACTIVE PROTEIN, INTERLEUKIN-6, D-DIMER, AND CONSEQUENT CARDIAC INJURY AND MORTALITY FOR PATIENTS WITH CORONAVIRUS DISEASE 2019: A META-ANALYSIS - ZAGEER, DHEAA SHAMIKH; HANTOOSH, SUNDUS FADHIL; Q SH. ALI, WATHIQ (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: This meta-analysis aims to investigate the role of high sensitivity-cardiac troponin I (hs-cTnI) as a prognostic factor for cardiac injury and as a risk factor of death for patients with coronavirus disease 2019 (COVID-19). This meta-analysis studies the impact of hs-cTnI elevated levels on C-reactive protein (C-RP) protein, interleukin-6 (IL-6), and D-dimer (DD) levels in COVID-19 affected individuals. Methods: Of 557 downloaded articles according to chosen criteria for this meta-analysis, 11 were finally chosen as they met the criteria. Results: Male and elderly individuals were noticeably prone to COVID-19 infection and considerably underwent death in comparison with female and young individuals. Levels of hs-cTn I, C-RP, IL-6, and DD were significantly higher among dead compare to survivors for COVID-19 affected individuals. Conclusions: Levels of C-RP, IL-6, and DD were considerably high and in linear relation with elevated hs-cTn I levels. Hs-cTn I can be considered a reliable marker for COVID-19 infection prognosis and potent predictor of decease.